2016
DOI: 10.3390/met6030051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cryogenic Forging and Anodization on the Mechanical Properties and Corrosion Resistance of AA6066–T6 Aluminum Alloys

Abstract: Abstract:In this study, AA6066 alloy samples were cryogenically forged after annealing and then subjected to solution and aging treatments. Compared with conventional 6066-T6 alloy samples, the cryoforged samples exhibited a 34% increase in elongation but sacrificed about 8%-12% in ultimate tensile strength (UTS) and yield stress (YS). Such difference was affected by the constituent phases that changed in the samples' matrix. Anodization and sealing did minor effect on tensile strength of the 6066-T6 samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The broken particles is clearly identified in the CF etched sample ( Figure 2f) located inside of a shear band. The same result was reported for cryogenic forged AA6066-T6 aluminum alloys [19]. The finer secondary particles in the CF sample presumably present stronger mechanical strength due to good obstructing and retarding dislocation movement.…”
Section: Initial Microstructure Characterizationsupporting
confidence: 83%
See 1 more Smart Citation
“…The broken particles is clearly identified in the CF etched sample ( Figure 2f) located inside of a shear band. The same result was reported for cryogenic forged AA6066-T6 aluminum alloys [19]. The finer secondary particles in the CF sample presumably present stronger mechanical strength due to good obstructing and retarding dislocation movement.…”
Section: Initial Microstructure Characterizationsupporting
confidence: 83%
“…They observed that MAF at cryogenic temperature showed a greater yield strength when compared to that obtained in the cryorolled samples. Shih et al [19] reported a significant increase in the tensile strength of the cryogenically forged AA6066 when compared with the T6 treated samples.…”
Section: Introductionmentioning
confidence: 98%
“…Forging Al alloys could offer good tensile strength (≥300 MPa) and high elongation (≥10%) and fatigue strength (≥120 MPa at 1 × 10 7 cycles) [11][12][13]. The forged parts are widely used in the automotive industry.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of the cast/forge process was proposed by Fujikawa et al [14] Chang et al introduced the cast/forge hybrid process to reduce the porosity of 7075 aluminum alloy castings [15]. The tripods produced with this process were shown at ALUMINUM CHINA 2018, Shanghai, New International Expo Centre (2018/07/ [11][12][13]. The block castings were used instead of extruded bars or plates to decrease the processing cost.…”
Section: Introductionmentioning
confidence: 99%
“…In [12], both room temperature and cryogenic forging operations were carried out on AA6066-T6 aluminium alloy workpieces. It was shown that the use of liquid nitrogen led to the formation of finer precipitates within the matrix, which improved the corrosion resistance after anodization, since a reduced number of particles, detrimental for the corrosion resistance, remained entrapped within the anodization film.…”
mentioning
confidence: 99%